Countdown 1945 : [large type] the extraordinary story of the atomic bomb and the 116 days that changed the world - Wallace, Chris; Weiss, Mitch (Thorndike Press large print nonfiction, 2020)
A "behind-the-scenes account of the 116 days leading up to the Americans attack on Hiroshima"--Dust jacket flap.